Six week consistency of sensorimotor test methods - Volery, S.; List, R.; de Bruin, E.; Jaeggi, M.; Baur, B.; Lorenzetti, S. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
The purpose of this study was to compare sensorimotor testing methods. Therefore 15 healthy and sporty subjects undertook five different sensorimotor tests and repeated the same tests six weeks later without executing any specific sensorimotor training. The main outcome was that movement unspecific and simple tests like the Counter Movement Jump, the maximum isometric force and rate of force development on a blocked leg-press or a single-leg-stance with closed eyes have a better retest-reliability than more specific movements like a balance test on a balance board or a complex movement like a single-legged jump landing. Tests with a specific movement show a learning effect and at complex movements there was almost no correlation, as slight changes in the motion sequence can lead to big differences in the measured scores.